NILAI LOKAL MASYARAKAT SUMBAWA SEBAGAI ACUAN KEBIJAKAN DAERAH MENGHADAPI COVID-19 (TINJAUAN YURIDIS-SOSIOLOGIS TERHADAP FORMULASI PENETAPAN SURAT EDARAN BUPATI SUMBAWA) - Lahmuddin Zuhri; Iwan Haryanto; Endra Syaifuddin (Indonesian Publication Center, 2020)
The emergence of polemics from various circles of society regarding the Circular of the Regent of Sumbawa with Number 900/125 / BPBD / V / 2020, so that the implementation of takbiran activities and Eid prayer 1 Syawal 1441 H are not carried out in congregation in the field or mosques and replaced with Eid and takbir prayers carried out at home with the nuclear family members or individually. Then the question arises, what is the background for the birth of the SE Regent of Sumbawa, then what is the juridical review of the Sumbawa Regent Circular. To study this problem, legal research methods with empirical aspects were used, with data collection using interviews, observation, and literature study. Then the data were processed using qualitative analysis. The results of the analysis, which led to the issuance of the Circular of the Regent of Sumbawa with Number 900/125 / BPBD / V / 2020, namely that Sumbawa Regency is the red zone of the Covid-19 pandemic with the following data on COVID-19 patients: 15 positive, 8 recovered, PDP 29 people, ODP 11 people. Considering the number and distribution of COVID-19 patient locations in the Sumbawa Regency, the implementation of Eid prayer 1441 H / 2020 M is not carried out in the congregation in the field or mosque and is replaced by Eid prayer at home in the congregation with core family members or individually. However, on the other hand, this effort was not accompanied by other policies in order to prevent the spread of the virus so that many places that did not because crowds were closed and controlled and instead became increasingly rampant. Then the Judicial Review of the Regent's Circular, that the SE violates statutory regulations, such as the UUD, Law Number 39 of 1999 concerning Human Rights and the Criminal Code.